2022
DOI: 10.1002/jso.26787
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 infection and its consequences among surgical oncology patients: A systematic analysis, meta‐analysis and meta‐regression

Abstract: We conducted this meta‐analysis to address the outcomes in cancer patients after oncologic surgery during COVID‐19 pandemic. The primary endpoint was the COVID‐19–related mortality rate. Higher body mass index was significantly and negatively associated with higher all‐cause mortality and in‐hospital COVID‐19 infection rates. Male sex, preoperative respiratory disease, and smoking history were positively and significantly associated with increased all‐cause mortality rates. Furthermore, male sex was positively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…6 A meta-analysis demonstrated that male sex, smoking history, and preoperative respiratory disease were positively associated with increased mortality in patients who underwent cancer surgery during the COVID-19 pandemic. 19 This study used propensity score Note: The data are expressed as number (%). a Compared with SARS-CoV-2 negative group, χ 2 test, p < 0.05 significant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 A meta-analysis demonstrated that male sex, smoking history, and preoperative respiratory disease were positively associated with increased mortality in patients who underwent cancer surgery during the COVID-19 pandemic. 19 This study used propensity score Note: The data are expressed as number (%). a Compared with SARS-CoV-2 negative group, χ 2 test, p < 0.05 significant.…”
Section: Discussionmentioning
confidence: 99%
“…An ASA Physical Status classification III–V was the only independent predictor of pulmonary complications 30 days after surgery 6 . A meta‐analysis demonstrated that male sex, smoking history, and preoperative respiratory disease were positively associated with increased mortality in patients who underwent cancer surgery during the COVID‐19 pandemic 19 . This study used propensity score matching to reduce the effects of confounding variables.…”
Section: Discussionmentioning
confidence: 99%